BARONG KUNTISRAYA (Sekilas Segi Estetisnya) - I Nyoman Putra Adnyana (Institut Seni Indonesia Surakarta, 2002)
Barong Kuntisraya, a dancing-role play performance, is a traditional Balinese one that makes the use of theme related to the Rwa Bineda myth. Balinese truly put their belief upon Rwa Bineda that becomes the myth. They are sure that the two distinctive or opposite powers appear side by side in the human life in the world. In its on-stage performance, it presents two enormous powers through the Barong showing the good and Rangda representing the bad.The peifo mance of Barong Kuntisraya is so interesting, either as the show or as the example on the ground that the reflected aesthetic expressions in the performance invites us to think and contemplate the various meanings behind the actions.Key Word: Aesthetic, Barong Kuntisraya.